Maintained peak leg and pulmonary VO2 despite substantial reduction in muscle mitochondrial capacity. (December 2015) - Boushel, R.; Gnaiger, E.; Larsen, F. J.; Helge, J. W.; González‐Alonso, J.; Ara, I.; Munch‐Andersen, T.; van Hall, G.; Søndergaard, H.; Saltin, B.; Calbet, J. A. L.
Abstract : We recently reported the circulatory and muscle oxidative capacities of the arm after prolonged low‐intensity skiing in the arctic (Boushel et al., 2014). In the present study, leg VO2 was measured by the Fick method during leg cycling while muscle mitochondrial capacity was examined on a biopsy of the vastus lateralis in healthy volunteers (7 male, 2 female) before and after 42 days of skiing at 60% HR max. Peak pulmonary VO2 (3.52 ± 0.18 L.min −1 pre vs 3.52 ± 0.19 post) and VO2 across the leg (2.8 ± 0.4L.min −1 pre vs 3.0 ± 0.2 post) were unchanged after the ski journey. Peak leg O2 delivery (3.6 ± 0.2 L.min −1 pre vs 3.8 ± 0.4 post), O2 extraction (82 ± 1% pre vs 83 ± 1 post), and muscle capillaries per mm 2 (576 ± 17 pre vs 612 ± 28 post) were also unchanged; however, leg muscle mitochondrial OXPHOS capacity was reduced (90 ± 3 pmol.sec −1 .mg −1 pre vs 70 ± 2 post, P  < 0.05) as was citrate synthase activity (40 ± 3 μmol.min −1 .g −1 pre vs 34 ± 3 vs P  < 0.05). These findings indicate that peak muscle VO2 can be sustained with a substantial reduction in mitochondrial OXPHOS capacity. This is achieved at a similar O2 delivery and a higher relative ADP‐stimulated mitochondrial respiration at a higher mitochondrial p50. These findings support the concept that muscle mitochondrial respiration is submaximal at VO2max, and that mitochondrial volume can be downregulated by chronic energy demand.